2000
DOI: 10.1074/jbc.m006756200
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Phosphorylation of the κ-Opioid Receptor Regulates Agonist Efficacy

Abstract: To explore the role of highly conserved tyrosine residues in the putative cytoplasmic domains of the seven-transmembrane G protein-coupled opioid receptors, we expressed the rat -opioid receptor (KOR) in Xenopus oocytes and then activated the intrinsic insulin receptor tyrosine kinase. KOR activation by the agonist U69593 produced a strong increase in potassium current through coexpressed G protein-gated inwardly rectifying potassium channels (K IR 3). Brief pretreatment with insulin caused a 60% potentiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 25 publications
0
10
0
1
Order By: Relevance
“…In addition, MOR contains four highly conserved cytoplasmic tyrosine residues (Thompson et al, 1993), and tyrosine kinase-mediated mechanisms regulating MOR signaling have also been described previously (McLaughlin and Chavkin, 2001;Zhang et al, 2009). Tyrosine phosphorylation may influence MOR trafficking and signaling (Pak et al, 1999), consistent with the effects of tyrosine phosphorylation on internalization and signaling of the ␦-and -opioid receptors (Kramer et al, 2000;Appleyard et al, 2000). A recent study by Law and colleagues showed that tyrosine phosphorylation of MOR at Tyr166 and Tyr336 controlled the switch from inhibition to stimulation of adenylyl cyclase after prolonged agonist application (Zhang et al, 2009).…”
mentioning
confidence: 79%
“…In addition, MOR contains four highly conserved cytoplasmic tyrosine residues (Thompson et al, 1993), and tyrosine kinase-mediated mechanisms regulating MOR signaling have also been described previously (McLaughlin and Chavkin, 2001;Zhang et al, 2009). Tyrosine phosphorylation may influence MOR trafficking and signaling (Pak et al, 1999), consistent with the effects of tyrosine phosphorylation on internalization and signaling of the ␦-and -opioid receptors (Kramer et al, 2000;Appleyard et al, 2000). A recent study by Law and colleagues showed that tyrosine phosphorylation of MOR at Tyr166 and Tyr336 controlled the switch from inhibition to stimulation of adenylyl cyclase after prolonged agonist application (Zhang et al, 2009).…”
mentioning
confidence: 79%
“…Opioid receptors can also be tyrosine phosphorylated. This modification affects desensitization as well, as has been shown in a series of studies examining C-terminal residues (Tyr96, Tyr106, Tyr166, and Tyr336) in the MOP-R (140), Tyr318 in the DOP-R (141,142), and residues in the first and second intracellular loop of the KOP-R (143). The net amount of receptor desensitization is thus controlled by many factors, which include phosphorylation, dephosphorylation, new receptor protein synthesis and secretion, as well as receptor endocytosis, recycling, and degradation (see below).…”
Section: Desensitizationmentioning
confidence: 90%
“…Phosphorylation of these residues has varying effects on the affinity of the protein for the GTP-bound form of G-proteins and modulates κ-opioid receptor signaling efficiency (30). Another important phosphorylation site is a serine residue (Ser 369 ) on the C-terminus.…”
Section: Regulation and Trafficking Of Kormentioning
confidence: 99%